Photothermal conversion enhancement of triangular nanosheets for solar energy harvest. (5th June 2020) - Wang, T.M.; Tang, G.H.; Du, M.
Highlights: Photo-thermal conversion enhancement of triangular nanosheets is investigated. Shape-induced tripolar resonance mode by triangular nanosheets benefits photo-thermal conversion. Blended nanofluids with silver triangular nanosheets and gold nanorods are proposed and tested. Blended nanofluids with 0.0001 vol% achieve a solar absorption efficiency of 76.9% experimentally. Abstract: Metallic plasmonic nanofluids have been adopted to enhance the photothermal conversion in direct absorption solar thermal collectors, however, their absorption band is not broad enough to realize a sufficient adsorption. Driven by the Local Surface Plasmon Resonance (LSPR) effect, this work explores the enhancement of triangular nanosheets in photothermal conversion, to facilitate the optimization of blended nanofluids. Firstly, the size effects of triangular nanoparticles on photothermal conversion are examined using the Discrete Dipole Approximation method. Then, the blended nanofluids based on silver triangular nanosheets and gold nanorods, are proposed and a high efficiency of 76.9% is achieved experimentally with a very low volume concentration (0.0001%). The enhancement mechanism is revealed furtherly by numerically investigating the excited electric field. We believe that this work can shed light on the design of blended nanofluids based on triangular nanosheets for solar energy harvest.